Degradação de fármacos residuais por processos oxidativos avançados - Melo, Silene Alessandra Santos [UNESP]; Trovó, Alam Gustavo [UNESP]; Bautitz, Ivonete Rossi [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP] (Sociedade Brasileira de Química, 2009)
The concern about aquatic ecosystems and the potential risk of drinking water contamination by pharmaceuticals have stimulated the study of processes for the efficient degradation of these contaminants, since the conventional treatment have been inefficient on that purpose. The advanced oxidation processes (AOPs) appear as viable alternatives due to their efficiency on the degradation of different classes of organic contaminants. This review presents an overview of the main AOP (O3, H2O2/UV, TiO2/UV, Fenton and photo-Fenton) which have been applied to the degradation of different pharmaceuticals. The main results obtained, intermediates identified and toxicity data are presented.
Degradation of residual pharmaceuticals by advanced oxidation processes
Keywords: micropollutants; advanced oxidation processes; sewage treatment plant